Adaptacje fabryki Franciszka Ramischa w Łodzi na OFF Piotrkowska – moda czy fenomen? - Pietrzykowska, Justyna (Lodz University of Technology Press, 2016)
The article is an attempt to address the question of character and reason in the adaptation of the post-industrial factory complex built by Franciszek Ramisch to OFF Piotrkowska in Lodz. Is it an intuitive action and general tendency or does it deserve to be called a phenomenon? Referring to foreign examples of similar adaptations presented in this study, the Lodz case seems to fit into the common trend, but retains its distinctness because it vividly reflects the post-industrial city of Lodz.
The adaptation of the post-industrial factory complex built by Franciszek Ramisch to OFF Piotrkowska in Lodz- trend or phenomenon?
Keywords: revitalization urbanized areas; revitalization process; rewitalizacja obszarów zurbanizowanych; proces rewitalizacji